Care seeking pathways of older adults with hip fracture in India: exploratory study protocol. Issue 1 (December 2015) - Tewari, Abha; Sahu, Kirti; Yadav, Lalit; Pati, Sanghamitra; Nallala, Srinivas; Webster, Premilla; Norton, Robyn; Rath, Santosh
Abstract Background The incidence of hip fractures in older adults in India is likely to increase dramatically in the coming decades as a result of an aging population and increasing life expectancy. Currently, more than 600, 000 adults over 60 years of age suffer a hip fracture annually in India. This paper outlines a protocol for a qualitative study investigating the care seeking behavior of older adults with hip fractures: to determine the processes in decision making, identify causes for delay in obtaining care, and identify potential barriers and facilitators to seeking appropriate care in time. Methods and design The planned study will consider Odisha, an eastern state in India with limited health care facility, as a suitable case study. It is proposed to conduct 30 in-depth interviews in two administrative districts of Odisha. The participants will be patient and their carers in seven health facilities- four public hospitals, two private hospitals and one traditional bone-setting facility. The study relies on a purposive sampling strategy. Ethics permission will be sought from each participating institution and participants. The participants will be adults aged 50 years or older of both sexes arriving at the recruiting centers with a history of fall or injury, pain in the hip region and inability to walk and X-ray confirmed diagnosis of proximal femoral fracture and their primary carer. Trained qualitative research team will conduct these interviews. A thematic framework approach will be used to analyze the data using NVivo 9 software. The data collected from the interviews will be analysed to explore the cause of the hip fracture, events following the injury, the experiences of patients from the time of sustaining the injury, pain relief measures, decision to seek care, understanding of the urgency for treatment, causes for delay in receiving treatment, funding sources, cost liabilities for the family, financing mechanisms for out of pocket expenditure and the burden for caring. Discussion The findings of this study will provide an increased understanding of the care seeking behaviors of older adults with hip fracture, and inform contextually appropriate changes in healthcare program and policy aimed at improving health outcomes.